The Impact of Self-Care Management on Systolic Blood Pressure Control in Hypertensive Patients - Faqih, Moh. Ubaidillah; Munir, Miftahul; Hakim, Lukman; Putri, Berlian Maharani Febrina (Journal of Pubnursing Sciences, 2025)
Background: Systolic blood pressure is an important indicator in the diagnosis of hypertension and plays a significant role in heart disease, stroke, and kidney failure. Hypertension can be managed through a healthy lifestyle and medication; however, consistency in applying self-care is a major challenge. Aims: To determine the relationship between self-care management and systolic blood pressure in hypertensive patients. Methods: A descriptive correlational study design with a cross-sectional approach was conducted with 112 hypertensive respondents. Self-care management data were collected using the Hypertension Self Management Behavior Questionnaire, and systolic blood pressure was measured with a digital sphygmomanometer. The data were analyzed using the Spearman test. Results: The majority of hypertensive patient had self-care management in the "adequate" category (44.6%), with half having systolic blood pressure between 140-159 mmHg. The Spearman test showed a significant relationship between self-care management and systolic blood pressure (ρ = 0.005, r = 0.262), indicating that better self-care management leads to more controlled systolic blood pressure, although the influence is weak. Conclusion: Good self-care management, including medication adherence, maintaining a healthy low-sodium diet, engaging in regular physical activity, maintaining an ideal body weight, effectively managing stress, avoiding alcohol consumption and smoking, and regularly monitoring blood pressure, has a significant relationship with systolic blood pressure control, although its effect is weak. Health education and social support need to be strengthened to improve self-management quality in hypertensive patients.